2018
DOI: 10.9734/ijpss/2018/41148
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Bacillus subtilis on Tomato Plants Growth and Some Biochemical Characteristics under Combined Application with Humic Fertilizer

Abstract: In this study we investigated the mechanisms of action and effect of plant growth promoting rhizobacteria (PGPR) Bacillus subtilis No.2 when utilized alone and in conjunction with a humic fertilizer (HF). Different mechanisms of action of B. subtilis No.2 and HF Stimulife on tomato plants Original Research Article

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
(40 reference statements)
3
4
0
1
Order By: Relevance
“…The highest amounts of individual and total organic acids were recorded in fully irrigated plants treated with TW, whereas the lowest overall values were observed under deficit irrigation for plants that received the XS treatment. This finding coincides with the report of Pishchik et al [58], who suggested that the application of Bacillus subtilis had a beneficial effect on the organic acid content of tomato fruit. In general, organic acid content decreased under water stress for all the biostimulant treatments compared to the respective treatments of fully irrigated plants, which suggests the small contribution of organic acids as osmoprotectants under stress.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The highest amounts of individual and total organic acids were recorded in fully irrigated plants treated with TW, whereas the lowest overall values were observed under deficit irrigation for plants that received the XS treatment. This finding coincides with the report of Pishchik et al [58], who suggested that the application of Bacillus subtilis had a beneficial effect on the organic acid content of tomato fruit. In general, organic acid content decreased under water stress for all the biostimulant treatments compared to the respective treatments of fully irrigated plants, which suggests the small contribution of organic acids as osmoprotectants under stress.…”
Section: Resultssupporting
confidence: 92%
“…The only exception was recorded in the untreated plants that received full irrigation, where chlorophyll b and total chlorophyll content was significantly lower than under specific treatments (e.g., TWW+, CW-and XSW-). Several reports suggest the beneficial effects of microbial biostimulants on the leaf chlorophyll content of various vegetables [58,64,[66][67][68][69], whereas, in fruit, this effect is expected to be lessened due to the gradual degradation of chlorophyll with ripening progression [70].…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, substantial efforts have been extended to the use of physiochemical and ecofriendly biological approaches, which are currently being applied to alleviate plant heat stress. Recently, the co-administration of HA and the Bacillus genus as important plant bio-stimulants that improve the growth and productivity in different crops [41,49] while reducing the dependency on chemical fertilizers has begun to gain importance. Previous reports demonstrated that humic substances may favor bacteria-plant interactions and enhance the bacterial attachment and colonization [47,74].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Busato et al [48] applied a microbial suspension and a humic substance to plant substrates to promote seedling adaptation to stressful environments. Pishchik et al [49] reported the impact of combined application of microbes and HA on tomato plants. However, least information are available on the combined effects of PGPB specifically endophytes and HA on tomato seedlings under heat stress conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The 1.5-kilobase partial sequence of the 16S rRNA gene was amplified using a polymerase chain reaction (PCR) and universal Eubacteria-specific primers: 8F (5 -AGAGTTTGATCCTGGCTCAG-3 ) and 1541R (5 -AAGGAGGTGATCCAGCCGCA-3 ). PCR experiments were conducted according to the protocol described in [95]. The PCR product was sequenced using the two primers given above and the following set of two forward and two reverse primers: 805R (5 -GGACTACCAGGGTATCTAATCCC-3 ), 515R (5 -GWATTACCGCGGCKGCTG-3 ), 508F (5 -AACTACGTGCCAGCAGC-3 ), 908F (5 -AAACTCAAAGGAATTGACGG-3 ).…”
Section: S Rrna Sequencing Of Pgpbmentioning
confidence: 99%